2011
DOI: 10.1371/journal.pone.0017177
|View full text |Cite
|
Sign up to set email alerts
|

Metabolites of Purine Nucleoside Phosphorylase (NP) in Serum Have the Potential to Delineate Pancreatic Adenocarcinoma

Abstract: Pancreatic Adenocarcinoma (PDAC), the fourth highest cause of cancer related deaths in the United States, has the most aggressive presentation resulting in a very short median survival time for the affected patients. Early detection of PDAC is confounded by lack of specific markers that has motivated the use of high throughput molecular approaches to delineate potential biomarkers. To pursue identification of a distinct marker, this study profiled the secretory proteome in 16 PDAC, 2 carcinoma in situ (CIS) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 76 publications
2
17
0
Order By: Relevance
“…ARHGDIA-a specific regulator of Rho protein exchange reactions crucial for JNK pathway-was previously identified by a bioinformatic pipeline that searched for candidate genes related to pancreatic cancer using protein-protein interactions and a shortest path approach [180]. Also, in accordance with our results, PARK7 was found to be significantly elevated in PDAC [181], correlated with tumor invasion and worse patients' outcome, and responsible for promoting invasion and metastasis of pancreatic cancer cells [182].…”
Section: Discussionsupporting
confidence: 84%
“…ARHGDIA-a specific regulator of Rho protein exchange reactions crucial for JNK pathway-was previously identified by a bioinformatic pipeline that searched for candidate genes related to pancreatic cancer using protein-protein interactions and a shortest path approach [180]. Also, in accordance with our results, PARK7 was found to be significantly elevated in PDAC [181], correlated with tumor invasion and worse patients' outcome, and responsible for promoting invasion and metastasis of pancreatic cancer cells [182].…”
Section: Discussionsupporting
confidence: 84%
“…Along with adenosine, which was detected originally, these all react with the enzyme purine-nucleoside phosphorylase, an enzyme with oncogenic effects when dys-regulated [33]. Further, metabolites of purine nucleoside phosphorylase have been found to be potential serum biomarkers in pancreatic cancer [34]. Thus the use of gene expression weighting has drawn attention to new metabolite concepts that were missed when the two data types were analyzed separately.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Roberts et al showed that plasma PNP activity was higher also in patients with breast, gastric, colon, lung and ovarian cancers and lymphoma (Roberts et al, 2004). From the biomarker perspective, Vareed et al found that PNP levels were higher in sera from pancreatic adenocarcinoma patients and levels of PNPregulated metabolites in serum, guanosine and adenosine, were suitable to determine pancreatic adenocarcinoma and distinguish pancreatic adenocarcinoma from benign tumors (Vareed et al, 2011). Plasma PNP activity was also higher in patients with asthma than in either healthy subjects or patients with gout (Yamamoto et al, 1995).…”
Section: Associated Pathologiesmentioning
confidence: 99%